Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1021/acs.nanolett.0c01627
|View full text |Cite
|
Sign up to set email alerts
|

Phonon Polaritons in Twisted Double-Layers of Hyperbolic van der Waals Crystals

Abstract: Controlling the twist angle between two stacked van der Waals (vdW) crystals is a powerful approach for tuning their electronic and photonic properties. Hyperbolic media have recently attracted much attention due to their ability to tailor electromagnetic waves at the subwavelength-scale which, however, usually requires complex patterning procedures. Here, we demonstrate a lithography-free approach for manipulating the hyperbolicity by harnessing the twist-dependent coupling of phonon polaritons in double-laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
102
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(119 citation statements)
references
References 40 publications
5
102
1
2
Order By: Relevance
“…Several samples with increasing rotation angles were fabricated, confirming hyperbolic-to-elliptic topological transitions, both reflected in the mapped near-field distribution (left, Figure 7F) and the obtained dispersion (right, Figure 7F) [25]. These results were also confirmed by other experiments [110,111]. Extreme dispersion engineering may stimulate new research in the field of 'opto-twistronics', based on stacking tBLs and multilayer polaritonic surfaces, with the opportunity for extreme light manipulation at the nanoscale based on a simple geometrical rotation.…”
Section: Direct Writing Photolithography Assemblysupporting
confidence: 80%
“…Several samples with increasing rotation angles were fabricated, confirming hyperbolic-to-elliptic topological transitions, both reflected in the mapped near-field distribution (left, Figure 7F) and the obtained dispersion (right, Figure 7F) [25]. These results were also confirmed by other experiments [110,111]. Extreme dispersion engineering may stimulate new research in the field of 'opto-twistronics', based on stacking tBLs and multilayer polaritonic surfaces, with the opportunity for extreme light manipulation at the nanoscale based on a simple geometrical rotation.…”
Section: Direct Writing Photolithography Assemblysupporting
confidence: 80%
“…The polaritonic iso‐frequency curves (IFCs, slices of the dispersion surface in frequency‐momentum space by a plane of a constant frequency ν) are described by open hyperbolas, giving rise to exotic and very intriguing optical phenomena, such as extremely high momenta [ 8 ] (as needed for electromagnetic field confinement), small group velocities, negative phase velocities [ 9 ] (with great potential for applications exploiting negative refraction and Doppler effects at the nanoscale [ 10,11 ] ), ultralong lifetimes, [ 3,12 ] and more recently, flat‐band canalization of topological polaritons in twisted vdW bilayers. [ 13–16 ]…”
Section: Figurementioning
confidence: 99%
“…Exploring these unusual phenomena is central in the developing field of quantum twistronics 4 , 5 . The concept of twistronics has been extended to include the study of nano-light properties in materials like TBG and twisted α -MoO 3 6 9 . Recently, it was shown that applying the ideas of twistronics to both 1D and 2D photonic moiré lattices in dielectric nanophotonic materials leads to slow-light effect 10 , 11 , light localization/delocalization phenomena 12 , and tunable resonant chiral behavior 13 .…”
Section: Introductionmentioning
confidence: 99%